Recovering Soils Affected by Iron Mining Tailing Using Herbaceous Species with Mycorrhizal Inoculation - Zanchi, Carin Sgobi; Batista, Éder Rodrigues; Silva, Aline Oliveira; Barbosa, Marisângela Viana; Pinto, Flávio Araújo; dos Santos, Jessé Valentim; Carneiro, Marco Aurélio Carbone (Water, air, and soil pollution, 2021)
The objective of this research was to evaluate a soil recovery strategy in soils that were affected by iron mining tailing using herbaceous species inoculated with Acaulospora morrowiae (arbuscular mycorrhizal fungus (AMF)). Tailings were collected on the banks of the Gualaxo do Norte river, one of the places impacted by the Fundão Dam rupture, where tailing layers that were more than one meter were deposited. The experiment was carried out in a greenhouse, using 6 kg pots of non-sterile reject, in a randomized block design in a 4 × 2 factorial scheme, with four cropping systems ( Urochloa ruziziensis single crop–RS; and intercropping cultivation: U. ruziziensis with Crotalaria spectabilis –R + C; U. ruziziensis with Guizotia abyssinica –R + G and U. ruziziensis with C. spectabilis and G. abyssinica –R + C + G), with two AMF inoculation conditions (with 200 A. morrowiae spores per pot, and no inoculation), with three replications and 100 days duration. The R + C and R + C + G systems presented the highest shoot dry matter (SDM) yields. Regarding root dry matter production (RDM), a variation of 9.2 g of pot −1 roots was observed between the R + C and R + G systems. Mycorrhizal colonization (MC) was higher in the cultivation system with the three herbaceous species, being the R + C + G system 52% higher than RS system. Spore density did not vary among treatments. Microbial carbon biomass was higher in the RS and R + G treatments when not inoculated. Basal respiration was also higher when not inoculated. Overall, the R + C + G system was more efficient than other systems in the accumulation of elements. The cultivation system with three herbaceous plants proved to be efficient in establishing itself initially in the iron mining tailings, being a viable alternative for the rehabilitation process.